Effect of BG-Lures on the Male Aedes (Diptera: Culicidae) Sound Trap Capture Rates. Issue 6 (8th July 2021) - Staunton, Kyran M; Goi, Joelyn; Townsend, Michael; Ritchie, Scott A; Crawford, Jacob E; Snoad, Nigel; Karl, Stephan; Burkot, Thomas R
Abstract: With global expansion of the two main vectors of dengue, Aedes aegypti (Linnaeus, Diptera: Culicidae) and Aedes albopictus (Skuse, Diptera: Culicidae), there is a need to further develop cost-effective and user-friendly surveillance tools to monitor the population dynamics of these species. The abundance of Ae. aegypti and Ae. Albopictus, and associated bycatch captured by Male Aedes Sound Traps (MASTs) and BG-Sentinel (BGS) traps that were unbaited or baited with BG-Lures were compared in Cairns, Australia and Madang, Papua New Guinea. Mean male Ae. aegypti and Ae. albopictus catch rates in MASTs did not significantly differ when deployed with BG-Lures. Similarly, males of both these species were not sampled at statistically different rates in BGS traps with or without BG-Lures. However, MASTs with BG-Lures caught significantly less male Ae. aegypti than BGS traps baited with BG-Lures in Cairns, and MASTs without BG-Lures caught significantly more male Ae. albopictus than BGS traps without BG-Lures in Madang. Additionally, BG-Lures significantly increased female Ae. aegypti catch rates in BGS traps in Cairns. Lastly, bycatch capture rates in BGS traps were not significantly influenced by the addition of the BG-Lures. While this study provides useful information regarding the surveillance of Ae. aegypti and Ae. albopictus in these locations, further development and investigation is required to successfully integrate an olfactory lure into the MAST system.